Exploring Professional Reasoning in Occupational Therapy: A Scoping Review of Recent Research - Ossandon-Perez, M (SAGE Publications Inc., 2025)
Background: Professional reasoning in occupational therapy has become a key line of research. Updating and analyzing recent publications is crucial for the discipline. The objective of the research was to describe new findings and changes in the characteristics of research on professional reasoning in occupational therapy between 2019 and 2023. Method: A scoping review was used with the aim of identifying the development and scope of the literature on professional reasoning in occupational therapy from 2019 to 2023. The review was conducted in five stages following the PRISMA-ScR guidelines. Results: Seventy-six articles were described in terms of their nature and volume under the following categories: specific fields of practice, educational strategies for professional reasoning, theoretical discussions, and instruments related to professional reasoning. New findings include two professional reasoning modalities, five practice-related areas, and intervention programs that had not been previously described. Additionally, there has been an increase in the use of mixed methods. Conclusion: This scoping review identifies the nature and volume of literature on professional reasoning in recent years. The study reveals consolidated research lines focused on practice and teaching, alongside new findings and changes observed in recent studies. © The Author(s) 2025.